Efeitos de erros sobre o estabelecimento de relações condicionais e sobre a formação de classes de estímulos equivalentes - Zamith, Clarisse (2016)
Research has shown inconsistent results about the effect of errors on discrimination learning. Two studies were conducted with the general purpose of verifying the effect of errors during the acquisition of one set of conditional discriminations upon the performance on a second set that had been learned with few errors. In both studies children of 6 to 8 years of age learned two sets of arbitrary relations between Greek letters. The first study sought to produce errorless learning by way of a sample stimulus shaping procedure. One group learned all relations with stimulus shaping. A second group learned the first set in this manner and the second set through trial and error. Both groups were then tested on the first set of relations. The percentage of correct responses was higher for the relations learned with stimulus shaping than for those learned with trial and error. However, no consistent differences between procedures were found with regards to the total number of errors in the acquisition of each discrimination, which made it difficult to evaluate the effect of errors in the acquisition of the second set of discriminations upon later performance on the first set. Study 2 was a systematic replication of Study 1. The stimulus shaping procedure was substituted by an instruction procedure, and participants were tested to check for emerging equivalence classes. Group 1 learned all stimulus relations through instruction. Group 2 received instruction for the first set of relations, and learned the second set through trial and error. Groups 3 learned all relations through trial and error. Children who learned relations with the instruction procedure made fewer errors in later tests and trials involving these relations than children from Groups 2 and 3, thus indicating the detrimental effect of errors in conditional discrimination learning. There were no clear differences between groups with regards to performance on equivalence tests. High scores on some equivalence tests and average scores on others suggest that some responses were being controlled by the S- and not the S+